Clinical factors associated with progression to dementia in people with late‐life depression: A cohort study of patients in secondary care: Epidemiology / Prevalence, incidence, and outcomes of MCI and dementia. (7th December 2020) - Mueller, Christoph; Peakman, Georgia; Karunatilake, Nishshanka; Seynaeve, Mathieu; Perera, Gayan; Aarsland, Dag; Stewart, Robert
Abstract: Background: Depression in later life is increasingly being recognised as a prodrome for the development of dementia. We aimed to investigate which clinical factors are associated with more rapid conversion from depression to dementia. Method: The South London and Maudsley NHS Foundation Trust (SLaM) Clinical Record Interactive Search (CRIS) was used to retrieve anonymised data on patients who were aged 65 years or older and received a diagnosis of depression in mental health services, followed by a diagnosis of dementia >3 months later. Predictors of accelerated dementia development were investigated including demographic factors, health status rated on the Health of the National Outcome scale for older people (HoNOS65+), depression recurrence, and treatments including psychotropic drugs and cognitive behavioural therapy (CBT). Result: In 806 patients with late‐life depression who later received a diagnosis of dementia, significant predictors of shorter time to dementia diagnosis in fully adjusted models were older age, male gender, higher deprivation, and HoNOS65+ subscales measuring depressed mood and cognitive problems. A diagnosis of recurrent depressive disorder was independently associated with a longer time to dementia diagnosis. Antipsychotic drugs and CBT were significantly associated with longer times to dementia diagnosis when adjusted for demographic factors and severity of mood and cognitive difficulties, but not in fully adjusted models. Conclusion: In older adults with depression and subsequent dementia diagnosed by mental health services, faster progression to a diagnosis of dementia was predicted by age and gender, new onset depression, and severity of depressive and cognitive symptoms.